Rate of intrapartum cesarean section and related factors in older nulliparous women at term. Issue 2 (2nd November 2017) - Muto, Haruka; Ishii, Keisuke; Nakano, Takahiro; Hayashi, Shusaku; Okamoto, Yoko; Mitsuda, Nobuaki
Abstract: Aim: The aim of this study was to determine the effect of maternal age on emergency cesarean section (CS) during labor, and to identify the independent risk factors for emergency CS. Methods: This was a retrospective cohort study using data from 2009 to 2014 from a tertiary perinatal care center in Japan. Inclusion criteria were maternal age ≥ 35 years, nulliparous singleton pregnancy at term and a cephalic presentation without indication of elective CS at onset of labor. The primary outcome was rate of emergency CS, while independent risk factors were elucidated using multivariate logistic regression analysis. Results: Of 953 women, 199 (20.9%) delivered by emergency CS. Rates of emergency CS were 18.3% (129/706) in women aged 35–39 years and 28.3% (70/247) in those aged ≥ 40 years ( P < 0.01). Adjusted odds ratios (95% confidence intervals) of independent risk factors were 1.50 (1.03–2.18) for maternal age ≥ 40 years, 1.51 (1.06–2.17) for body mass index ≥ 25 kg/m 2, 2.22 (1.24–3.98) for hypertensive disorder during pregnancy, 3.43 (1.31–8.95) for large‐for‐date fetus and 4.64 (3.23–6.69) for induction of labor. Conclusions: The rate of intrapartum emergency CS in older nulliparous women at term was approximately 21%. Induction of labor should be recognized as a significant factor for emergency CS.